2015
DOI: 10.3233/jad-142871
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Risk for Conversion from Mild Cognitive Impairment to Alzheimer's Disease in an Elderly Arab Community

Abstract: In this population, age, female gender, lack of formal education, and hypertension are risk factors for both AD and MCI. Conversion risk from MCI to AD could be estimated as a function of age, time interval between examinations, and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Previous reports showed that people who reverted from MCI to normal cognition were younger, which is consistent with the results of the present study . However, sex was not previously associated with reversion to normal cognition or progression to dementia, which differs from our findings . These results might differ because the present study was an intervention study rather than an observational study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous reports showed that people who reverted from MCI to normal cognition were younger, which is consistent with the results of the present study . However, sex was not previously associated with reversion to normal cognition or progression to dementia, which differs from our findings . These results might differ because the present study was an intervention study rather than an observational study.…”
Section: Discussionsupporting
confidence: 87%
“…5,16 However, sex was not previously associated with reversion to normal cognition or progression to dementia, which differs from our findings. 5,16,17 These results might differ because the present study was an intervention study rather than an observational study. However, as this study did not include a control group, it was not clear whether there was a sex difference in the improvement of cognitive function by exercise training.…”
Section: Discussionmentioning
confidence: 78%
“…The prevalence of mild cognitive impairment in Taiwan was higher in women than that in men after adjusting for age, education level, and other common associated factors [24]. Similar findings were reported in several other studies [25,26]. Consistent with these studies' results, we found that the prevalence of CIND in northern China was higher in women than in men, with prevalence rates of 26.1% for women and 19.8% for men.…”
Section: Discussionsupporting
confidence: 81%
“…Another study surveyed elderly aged 65 years or older in an Arab community in Israel. Of the 231 subjects with MCI that were re-examined after 1 year, 68 (23%) converted to dementia, including 65 AD cases [10] . These studies, however, were either with short follow-up period or with vague diagnosis based on insufficient neuropsychological tests (e.g., MMSE only).…”
Section: Discussionmentioning
confidence: 99%